A Comparative Study of Oral Dexmedetomidine versus Oral Midazolam As preanesthesia Medication in Pediatric Patients to Reduce anxiety - Thapa, Chitra; Prasai, Abha (Birat Journal of Health Sciences, 2019)
Introduction: Preoperative period is a stressful period. In children the preoperative anxiety is expressed as difficult separation from parents and difficult mask induction. The level of preoperative anxiety also affects postoperative outcomes. To overcome anxiety premedication is often used by pediatric anesthesiologist.Objective: The objective of this study was to compare the effect of oral midazolam 0.5mg/kg and oral dexmedetomidine 4μg/kg on parental separation, mask induction and postoperative emergence agitation in children undergoing elective surgery under general anesthesia.Methodology: 120 children aged 2-8years undergoing elective surgery under general anesthesia were divided into two groups: Group M and Group D. Patients in group M received oral midazolam 0.5mg/kg and patients in group D received oral dexmedetomidine 4μg/kg. After 45min of premedication sedation score was assessed in both the groups. Ease of parental separation and mask acceptance was compared in both the groups. In the postoperative period occurrence of emergence agitation was compared in both the groups.Results: There was no statistically significant difference in preoperative sedation score in both the groups. Parent separation anxiety score and mask acceptance score were statistically similar in both the groups. But emergence agitation was significantly lesser in patients who received dexmedetomidine premedication.Conclusions: Premedication with oral midazolam as well as oral dexmedetomidine effectively reduces parental separation anxiety and produces satisfactory mask induction in pediatric age group. However, dexmedetomidine is more effective in reducing emergence delirium in comparison to midazolam.